HUBUNGAN KEBIASAAN MEROKOK DAN KEBIASAAN OLAHRAGA DENGAN KEJADIAN HIPERTENSI PADA PASIEN LANJUT USIA DI PUSKESMAS KELAYAN TIMUR BANJAMASIN - Zuhrupal Hadi; Edy Ariyanto (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Hypertension gives symptoms that will continue a little market target organs, such as stroke (to the brain), coronary heart disease (for coronary arteries) and hypertrophy of the right ventricle/left ventricle hypertrophy (for the heart muscle). The general objective of this study was to determine the relationship between smoking and exercise habits to the incidence of hypertension in elderly patients at the Health Center of East Kelayan Banjarmasin.In this study using analytical survey method with cross sectional approach. Accidental sampling with sampling techniques. Data collection using interviews through questionnaires, data analysis using Chi-Square test with a significance level (α) = 10 %. The data collected were analyzed using statistical univariate, bivariate analysis using chi square test with the help of computerization. The results obtained by analysis of the respondents who had diarrhea in Puskesmas kelayan Timur Banjarmasin city as much as 54.2%. Variables significantly associated with the incidence of diarrhea (p <0.1) is exercise habits. Advice can be given in this study is to health centers for improvement of East Kelayan extension given to increasing public knowledge increases. For the elderly who need to avoid developing hypertension risk factors hypertension. For further research are expected to conduct research on other risk factors.